The Last Twenty-One Years of Landscape Management in the Forest-Savannah Transition Zone: Case of Ngoro Municipality in Cameroon - Cedric, Chimi; Karol Lavoine , Mezafack; Parfait, Nkontcheu Kamta; Stelle, Pougom Vartant Djeukam; Banabas, Neba Nfornkah; Serges, Ndzie Okala; Nyong, Princely Awazi; Kevin, Tchemmoe Fokou; Katty Claudia , Chiteh; Bumtu, Kamah Pascal; Tanougong, Armand Delanot (Anuário do Instituto de Geociências, 2024)
In recent decades, environmental challenges have increased with climate change, which is strongly linked to the pressure of human activities with a consequence on natural landscape change. Based on the forest-savannah transition zone of Cameroon, the aim of this study is to analyze the last twenty-one years management of the Ngoro municipality landscape by the government; and also, analyze the local people impact on these landscapes. The spatio-temporal dynamics of the Ngoro landscape was measured using two Landsat images (TM 2000 and OLI from 2021) downloaded free and analysed with ENVI software based to the supervised classification algorithm. The cartographic approach was combined with surveys conducted with 152 key informants through a questionnaire. Results revealed that, the natural forest cover has experienced a regressive dynamic over 21 years (2000–2021). Seven land cover classes were identified namely old forest, shrubland and grassland, bare soil/slash and burn areas, plantation/agroforestry systems, urban, water surface and croplands. Forests and savannah which are the natural landscape have decreased in the twenty-one years under study, at a rate of -165 ha/year and -525 ha/year respectively, while bare soil and slash and burn areas (+183 ha/year), and crop land (+229 ha/year) have increased. Concerning landscape management, in the twenty-one years under study, 8% of the area has been allocated as community forest. The remaining 92% that has not been allocated is managed by the community. The community established farms (44%), inherited their parents’ farms (37%), bought land (10%) or received land as a gift (8%). The Ngoro municipality with its High Conservation Value potentials, harbours several endangered species, requires further empirical studies that can help identify biodiversity hotspots which will be beneficial for conservation. There is also the need to integrate indigenous Cameroonian initiatives that enhance sustainable landscape management practices.